An approach to the generation of simple analogues of the antitumour agent spicamycin. - Mons, S; Fleet, G (2003)
The one-step glycosylation of arylamines in acidic medium is extended to adenine derivatives for the first time, providing a considerable improvement over existing reactions. This method is used to prepare some rhamnospicamycin analogues containing different base moieties. Results suggest that this novel approach will be applicable to a wide range of carbohydrates and arylamines, possibly leading to a combinatorial library of analogues of spicamycin for the better understanding of the modes of action of this antitumour antibiotic family.